Islam, Christianity, and secularism in Bulgaria and Eastern Europe: the last half century - Evstatiev, Simeon; Eickelman, Dale F. (Social, economic and political studies of the Middle East, 2022)
"Is there a "return to the religious" in post-Communist Eastern Europe that differs from religious trends in the West and the Middle East? Looking beyond immediate events, this book situates public talk about religion and religious practice in the longue durée of the two entangled pasts -Byzantine and Ottoman-that implicitly underpin contemporary politics. Islam, Christianity, and Secularism situates Bulgaria in its wider region, indicating ongoing Middle Eastern, Russian, and other European influences shaping patterns of religious identity. The chapters point to overlapping and complementary views of ethno-religious belonging and communal practices among Orthodox Christians and Muslims throughout the region. Contributors are Dale F. Eickelman, Simeon Evstatiev, Kristen Ghodsee, Galina Evstatieva, Ilia Iliev, Daniela Kalkandjieva, Plamen Makariev, Momchil Metodiev, Daria Oreshina, Ivan Zabaev and Angeliki Ziaka"--